Postkolonialisme dalam Novel Air Mata Api Karya P.A. Redjalam - Raini, Ela Ang; Andriyani, Noni (UIR PRESS, 2023)
This study aims to reveal the forms of mimicry and subaltrends in the novel Air Mata Api by P.A. Redjalam. Mimicry forms and subaltrends can be described using views from Homi.K. Bhabha and Gayatri Spivak as the scalpel. The data of this research were processed by the stages of identification, classification, analysis, and interpretation as well as a description of the findings. The objects of this study are words, phrases, clauses, sentences and paragraphs that contain mimicry and subaltrend forms. The results of this study indicate that, first, mimicry in the novel Air Mata Api by P.A.Redjalam is found in the forms of thoughts, attitudes, and behaviors that use imitation by the colonized to be able to feel that they have power and are in a higher position than the colonized. other. The two forms of subaltrance found in the novel Air Mata Api by P.A. Redjalam are found in the form of physical and psychological violence perpetrated by the colonized. The physical and psychological violence that was carried out by the colonized was oppression, namely by hitting, kicking, choking and sexually abusing women which made the terjah feel that, by carrying out this oppression, the colonized felt that they had power.